TQM and ISO 9001 Adoption at the Authority of the Freeport Area of Bataan - De Leon, Patrick C. (Philippine Journal of Labor and Industrial Relations, 2023)
This case study was conducted to investigate why and how total quality management (TQM) and ISO (International Organization for Standardization) 9001 were adopted at the Authority of the Freeport Area of Bataan (AFAB); what TQM and ISO 9001 meant to its officials and staff; and what factors affected their implementation. A survey of 17 AFAB officials and staff involved in TQM and ISO 9001 implementation and site observations were conducted from November to December 2019. The study found that TQM and ISO 9001 were adopted to comply with Administrative Order No. 161 and Executive Order No. 605 of President Gloria Arroyo, and Memorandum Circular No. 2015-1 of the Department of Budget and Management, and improve the AFAB’s processes of registration, import and export and work force control. Implementation involved hiring of a consultant, conducting an orientation, constituting an ISO technical working group, training, creating a quality management system (QMS) manual, reviewing and streamlining work processes, conducting internal and external audits and management review, implementing corrective actions, and receiving an ISO 9001 certificate. To AFAB’s officials and staff, TQM meant having a QMS that ensures the delivery of quality services to customers, while ISO 9001 meant a QMS standard or a standardization of work processes. Top management support, employee dedication and citizen’s charter implementation positively affected TQM and ISO 9001 adoption. On the other hand, tight schedules, Bataan-wide expansion of the AFAB’s operations, and employees’ resistance to change negatively affected the adoption. The study recommends: (1) succeeding schedules that are more realistic and inclusive of the AFAB’s expanded operations; and (2) a program that simultaneously minimizes resistance to change and promotes internalization of TQM and ISO 9001 concepts.